The initial geography teacher training in Brazil and Portugal: aspects of the constitution of professional teacher identity - Maria Anezilany Gomes do Nascimento; Sérgio Claudino Loureiro Nunes (Universidade Federal de Santa Catarina, 2018)
This paper aims to treat the initial teacher training of geography in Brazil and Portugal, considering: the national curricular guidelines and the law-decrees which in the two countries legislate on this formation, guided by the international guidelines; a look at the articulation between the territorial and educational fields of training, namely the school and the university, especially in the scope of the institutional projects that guide the training. Based on four undergraduated degrees in Geography in Ceará and two master degrees in Lisbon, Portugal, the study involves a documentary analysis of the legislative documents that guide the professionalization of teaching. It is hoped to contribute to the reading of fundamental aspects about this initial teacher training, which relate to the constitution of the professional teacher identity by means of an effective theoretical-practical approach.